Causal relationship between ischemic stroke and its subtypes and frozen shoulder: a two-sample Mendelian randomization analysis - Lv, Xiaofeng; Hu, Zeng; Liang, Fangqi; Liu, Shanshan; Gong, Haiping; Du, Jihang; Deng, Xinmin; Qian, Jun-Hui; Nie, Qian; Luo, Jian (Frontiers in Neurology, 2023)
Background Previous epidemiological and other studies have shown an association between ischemic stroke (IS) and frozen shoulder (FS). However, the causal relationship between them remains unclear. Therefore, the present study aimed to investigate the causal relationship between IS and FS using a two-sample Mendelian randomization method. Methods Our research was divided into two stages: discovery and replication. The data were extracted from publicly available genome-wide association studies (GWAS). We selected a large sample of IS (n = 440, 328) and its subtypes (large-artery atherosclerotic stroke (LAS), cardioembolic stroke (CES), and stroke caused by small-vessel disease (SVS) and lacunar stroke (n = 254, 959) as exposure data. Additionally, we selected a large sample of FS as outcome data (n = 451, 099). Inverse variance weighting (IVW) was applied as the primary analysis method. The weighted median, MR-Egger, simple model, and weighted model were used as complementary analysis methods to assess causal effects. Moreover, heterogeneity was analyzed using Cochran's Q-test with IVW and MR-Egger. The MR-Egger intercept and MR-PRESSO analysis methods were used for pleiotropy testing. The stability of the results was also assessed using a leave-one-out analysis. Results In the discovery stage, the IVW approach revealed an odds ratio (OR) of 1.207 with a 95% confidence interval (CI) of 1.027–1.417 and a P-value of 0.022. This suggests a causal association between IS levels and an increased risk of FS. In the subtype studies of IS, the findings were negative. However, during the replication stage, a significant causal link was found between selected lacunar strokes and FS with an OR of 1.252, a 95% CI of 1.105–1.419, and a P-value of 0.0004. All studies had no pleiotropy or heterogeneity, and the findings were robust. Conclusions Our study confirmed the causal relationship between any IS level and increased risk of FS. Furthermore, the same results were obtained in the replication stage with lacunar stroke as an exposure factor. However, there was no direct causal relationship between the subtypes of IS and FS. Our study provides theoretical support for shoulder care for patients with IS.